-3(x-3)+3=6

Simple and best practice solution for -3(x-3)+3=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x-3)+3=6 equation:


Simplifying
-3(x + -3) + 3 = 6

Reorder the terms:
-3(-3 + x) + 3 = 6
(-3 * -3 + x * -3) + 3 = 6
(9 + -3x) + 3 = 6

Reorder the terms:
9 + 3 + -3x = 6

Combine like terms: 9 + 3 = 12
12 + -3x = 6

Solving
12 + -3x = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + -3x = 6 + -12

Combine like terms: 12 + -12 = 0
0 + -3x = 6 + -12
-3x = 6 + -12

Combine like terms: 6 + -12 = -6
-3x = -6

Divide each side by '-3'.
x = 2

Simplifying
x = 2

See similar equations:

| 6x-10+3x=0 | | -8(-x-6)+10=-2 | | 1208-41x=14x+53 | | -8(-x-6)+10=2 | | 5h(t)=7t-t^2 | | 12y-2=13y+4 | | 9x^2+x-22=0 | | 6-4=6x-8x+8 | | 3(2x-3)+2=3 | | 10x-9=2-5x | | 4x-2=13y+4 | | 7x-13-4x=7x-6 | | x^2-12x+228=0 | | 6x(3x+10)=14 | | 2x+2(x-6)=8x-6(x-10) | | 13xy+14y^2=0 | | 4x+4=-23+x | | lg(3x+4)=2 | | -1+5x=-7x+83 | | -6(1-4a)=66 | | 5x+4=-24+x | | x^6+8x^3-6=0 | | 4x*2+10x+10x+25= | | 0.5h+3=0.7h-3 | | 0.4x-0.2(x+4)=1.4(x+2) | | h=-16t^2+53 | | X^2-15x+5000=0 | | 2x+15=3x+c | | 3+5x+4=17 | | 11(k-1)=7(k-6.333333333) | | 11(k-1)=7(k-6.3333333333) | | 20=44-8(2x-x) |

Equations solver categories